Penerapan Ilmu Tajwid Al-Qur’an Kepada Siswa Kelas VII Di Sekolah MTs. Al-Jam’iyatul Washliyah Tembung - Nisah Nirwana Sinaga; Muhammad Qorib (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2023)
This form of activity is an effort to increase interest in reading the Qur'an to students' children by giving advice through words, praying for students, praise as motivation, sincere love, not overdoing it in giving advice, and gradual habituation. Factors inhibiting the lack of interest in reading the Qur'an are family factors, how parents educate their children, school environmental factors, especially peer interactions. The aim and hope of this activity is that children can better understand the science of recitation, students are motivated to learn the Qur'an. so that it is easier for students to improve their reading of the Al-Qur'an or Iqra'.